مؤسسة القرض الحسن بوصفها استراتيجية للحد من الفقر في أفغانستان: نموذج مقترح في ضوء تجربة ماليزيا: (The Qard al-Hasan Institution as a Strategy for Poverty Alleviation in Afghanistan: A Proposed Model in light of the Malaysian Experience) - جمال الدين حميدي; محمد أبو الليث الخيرآبادي (At-Tajdid - Intellectual Refereed Journal, 2025)
Microfinance institutions represent an effective tool that has proven successful globally in combating poverty. However, their implementation in Afghanistan, due to contradictions with Islamic principles, has not contributed to solving the problem of poverty but has instead exacerbated it. Accordingly, this study aims to present a model for a microfinance institution based on the Qard al-Hasan (interest-free loan) principles as a strategy to alleviate poverty and achieve sustainable development in Afghanistan. The proposed model integrates Qard al-Hasan mechanisms with waqf (endowment), zakat, and takaful (solidarity), drawing insights from successful experiences in Islamic microfinance, particularly the Malaysian experience. The model relies on diverse funding sources, including cash waqf, hujaj (pilgrim) deposits, donations, zakat funds, proceeds from sacrificial animal skins, customer deposits, permissible service revenues, profitable investments, and governmental support, enhancing the institution’s financial sustainability. The study aims to clarify the concept and significance of Qard al-Hasan in light of Islamic texts, emphasizing the necessity of establishing an official institution to implement Qard al-Hasan as a tool to combat poverty in Afghanistan. Additionally, it provides a practical model for a Qard al-Hasan institution integrated with waqf, zakat, and takaful to help reduce poverty in Afghan society. aimed at poverty alleviation in Afghan society. The research employs an inductive approach to examine successful experiences, the field method for collecting primary data, the descriptive method to explain concepts, and the analytical method for data analysis to determine a suitable model for implementation in Afghanistan. Key findings suggest that a Qard al-Hasan institution, if implemented within an appropriate legislative and administrative framework, could play an effective role in reducing poverty and unemployment, and in creating sustainable job opportunities through interest-free microloans for the neediest segments of society. The study recommends adopting policies to support this model’s implementation and conducting further research on developing Islamic finance and its institutions in Afghanistan. Keywords: Qard al-Hasan, Islamic microfinance, poverty, Afghanistan.